Urban Forestry in Kota Kinabalu: Home Garden practices by urban villages for biodiversity, socio-economic and environmental services. Issue 1 (1st February 2023) - Kodoh, J; Jaunis, O; Maid, M; Lintangah, W; Mojiol, A R
Abstract: The growing urbanization has greatly reduced biodiversity. Home gardening is a crucial approach for biodiversity preservation, particularly in metropolitan settings with a dearth of green spaces. The goal of this study is to determine the types of trees and crops growing in urban villages in Kota Kinabalu, as well as the socioeconomic and environmental benefits that urban residents receive from their home gardens, which serve as urban forests. In four urban villages, the data were gathered through observation and household questionnaires. Interviews have been conducted with 217 respondents in total. The results showed that the respondents planted a total of 14 different crop and tree types, with Misai Kucing ( Orthosiphon stamineus ) and mango tree ( Mangifera spp .), Pandan ( Pandanus sp .) and Red Onion ( Allium ascalonicum ) being the most popular trees and crops. The garden's key contributions were lowering the temperature in the residential areas and as a leisure activity area. There was little correlation between the social benefit of urban forestry and the function of home gardens such as for food supply, medicinal use and hobby. Due to the small-scale home gardens, the economic contribution was little but complemented domestic requirements. The promotion of agroforestry systems in urban areas needs to be stepped up to preserve biodiversity, meet the demand for food and medicine, and provide environmental benefits.